Exploring the Perspectives of Young Adults on Cervical Cancer Screening in the Western Region of Ghana: A Qualitative Enquiry - Pearce, Betty; Aziato, Lydia; Achempim-Ansong, Gloria (Asian Pacific Journal of Cancer Care, 2023)
Background: Cervical cancer is a major public health issue globally. In Ghana, there is paltry of information on the perspectives of young adults on cervical cancer. Aim: The study explored the perception of young adults between the ages of 17-24 on cervical cancer screening at a hospital in the Sekondi-Takoradi Metropolis of the western region of Ghana. Methods: Qualitative exploratory descriptive method was employed in this study. 13 participants who met the inclusion criteria were purposively selected for the study. Respondents were interviewed face-to-face using a semi structured interview guide designed based on the research objectives. All interviews were audio taped, transcribed verbatim and analysed using thematic content analysis. Results: Younger adults had adequate knowledge on cervical cancer but inadequate information on its screening methods. All young adults in the study had never done screening because they did not see themselves susceptible to the development of cervical cancer and some opined that, cervical cancer is a disease for older and pregnant women. Conclusion: Participants had an incorrect perception on cervical cancer screening so more education should be put in place in our institutions to increase their knowledge on the dangers of cervical cancer and the screening methods available in its prevention.